2017
DOI: 10.1149/08008.1005ecst
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Carbonate Formation Kinetics and Morphological Effects Observed on OH-Form of Pfaem When Exposed to Air Containing CO2

Abstract: For AEMFC, OHform of membrane reacts with CO2 when exposed to air leading to loss in conductivity. Very few attempts have been made to understand the reaction kinetics, morphological properties and equilibrium concentrations at different environmental conditions. We have attempted to study the CO2 kinetics and its effect on water-uptake (or lambda) and morphology(SAXS) when the OHform of membrane is exposed to air which has approx. 400 ppm of CO2. The kinetics was studied by exposing the membrane to controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 4 publications
(5 reference statements)
0
17
0
Order By: Relevance
“…It is widely understood that these reactions occur quickly . It can be problematic to accurately calculate their intrinsic rate because, in relevant systems, the transformation may be limited by CO 2 mass transport.…”
Section: Effect Of Co2 On Oh− In Aemsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely understood that these reactions occur quickly . It can be problematic to accurately calculate their intrinsic rate because, in relevant systems, the transformation may be limited by CO 2 mass transport.…”
Section: Effect Of Co2 On Oh− In Aemsmentioning
confidence: 99%
“…It is widely understood that these reactions occur quickly. [10,[17][18][19][20] It can be problematic to accurately calculate their intrinsic rate because, in relevant systems, the transformation may be limited by CO 2 mass transport. Yanagi and Fukuta found that, for an A201 AEM (Tokuyama Corp.,Japan), the OH À concentrationd ecreased by about 90 %i nt he first 10 min of exposure to air,f orming CO 3 2À .…”
Section: Effect Of Co 2 On Oh à In Aemsmentioning
confidence: 99%
“…OH − water uptake was only measured for the PFAEM_CH3_C6 polymer because it was the only material stable enough to survive this measurement. In this polymer, the λ values for the OH − form are higher than in the Cl − form . We also notice that the λ value is almost half of the Nafion®‐117 .…”
Section: Resultsmentioning
confidence: 69%
“…The temperature was increased from 30 to 80 °C and relative humidity of the chamber was kept constant at a 95% RH value. For the OH − conductivity, the AEM samples were soaked in aqueous 1M KOH solution in a N 2 environment glove box, which is CO 2 free as the OH − in AEM reacts with CO 2 in air to form carbonate/bicarbonate . The samples were soaked for 24 h and washed with degassed DI water four times in 24 h after alkali treatment still in the CO 2 free glove box.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation